Genome-wide association study of knee osteoarthritis: present and future - Takuwa, Hiroshi; Uchio, Yuji; Ikegawa, Shiro (Annals of Joint, 2018)
Knee osteoarthritis (KOA) is a complex disease. Although the genome-wide association study (GWAS) has elucidated many KOA susceptibility genes, they explain only a small part of heritability of KOA and their replicability is low. The sample size and phenotype definition are important factors to improve statistical power of the GWAS. The low replicability of the KOA GWASs would be mainly caused by their small sample size and the indistinct definition of KOA. We seek to establish the more distinct KOA definition to improve OA GWAS. We reveal the effectiveness of the ultrasonography (US) to evaluate the early change of OA cartilage and conduct the epidemiological study of KOA defined by US in a cohort (Shimane COHRE study). Now we are performing the GWAS for early KOA based on the cohort study.